2008
DOI: 10.1590/s0100-46702008000100001
|View full text |Cite
|
Sign up to set email alerts
|

The physico-chemical properties of 4-chlorophenoxyacetates of Mn(II), Co(II), Ni(II) and Cu(II)

Abstract: The complexes of 4-chlorophenoxyacetates of Mn(II), Co(II), Ni(II) and Cu(II) have been synthesized as polycrystalline solids, and characterized by elemental analysis, spectroscopy, magnetic studies and also by X-ray diffraction and thermogravimetric measurements. The analysed complexes have the following colours: pink for Co(II), green for Ni(II), blue for Cu(II) and a pale pink for Mn(II) compounds. The carboxylate group binds as monodentate and bidentate ligands. On heating to 1173K in air the complexes dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…4 The complexes of Nd(III), Gd(III) and Ho(III) ions with the 2-(4-chlorophenoxy)acetic acid anion are di-and trihydrates 14,15 and they exhibited properties similar to those of the complexes described in this paper. Therefore, the magnetic moment value of the Er(III) complex was equal to 7.01 (1.8 K) and 8.94 μ B (48 K).…”
Section: Magnetic Propertiesmentioning
confidence: 54%
See 2 more Smart Citations
“…4 The complexes of Nd(III), Gd(III) and Ho(III) ions with the 2-(4-chlorophenoxy)acetic acid anion are di-and trihydrates 14,15 and they exhibited properties similar to those of the complexes described in this paper. Therefore, the magnetic moment value of the Er(III) complex was equal to 7.01 (1.8 K) and 8.94 μ B (48 K).…”
Section: Magnetic Propertiesmentioning
confidence: 54%
“…1 They serve for the production of biomedical materials and as the therapeutic agents being used in anti-cancer therapy. 14,15 In previous papers, studies of the 2-(4-chlorophenoxy)acetic acid anion with Mo, Li, Cu, Mn, Co, Ni, Nd, Gd and Ho were reported in which the complexes were characterized by elemental analysis, FTIR spectroscopy, thermogravimetric studies and X-ray diffraction measurements. Having luminescence properties, their complexes with 4f electron elements find application in optical and electronic industries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IR spectroscopy for the Cu(II) complex and for sodium salt of 4‐nitrocinnamic acid and spectroscopic criteria indicated that COO – group coordinates monodently to the metal cation. XAFS studies confirmed the coordination via COO – groups and specified that the polyhedron of Cu(II) exhibits a square‐planar geometry (CuO 4 ) with two carboxylate ligands coordinating in the monodentate mode and two aqua ligands (Fig.…”
Section: Discussionmentioning
confidence: 99%